Effect of Ileal Transposition (IT) on Angiopoietin-Like Protein-8 (ANGPTL8) and Pentraxin (PTX3) Plasma Level in Sprague-Dawley Rats Fed High-Fat Diet (HFD) - Tomasz Sawczyn; Dominika Stygar; Katarzyna Nabrdalik; Michał Kukla; Oliwia Masri; Łukasz Magrowski; Wojciech Karcz; Jerzy Jochem (International Journal of Endocrinology)
Background. Metabolic surgery procedures are designed not only for sustained weight loss but also for achieving positive metabolic changes, including improved glucose tolerance and insulin sensitivity, along with an increase in energy expenditure. Based on recent findings, the present study focuses on the relationship between the effects of ileal transposition (IT), high-fat diet (HFD), and selected markers of lipid metabolism and inflammation. Methods. Forty-eight male rats were divided into two groups: HFD and control diet (CD) fed rats. After eight weeks, animals in each group were randomly assigned to two types of surgery: IT and SHAM. Thereafter, fifty percent of the animals in the HFD and CD groups had their diets changed, while the remaining half maintained their presurgery diets. Eight weeks after surgery, plasma levels of ANGPTL8, PTX3, leptin, and adiponectin were assessed. Results. The IT group pre- and postoperatively maintained on the HFD showed higher ANGPTL8 level compared to SHAM operated animals (p=0.0041). The effect of IT on PTX3 level in the group pre- and postoperatively maintained on a CD was not significant, and there were no differences compared to SHAM. Only the postoperative diet change to HFD increased PTX3 level in the IT operated animals (p=0.0002). The IT group had increased plasma adiponectin (p=0.026) and leptin (p=0.0027) levels after dietary change to HFD compared to IT rats fed CD. Conclusions. This study indicates that the outcomes of metabolic surgery can be greatly modified by HFD. The effects of the IT procedure in this experiment are ambiguous and do not provide a clear answer as to whether or not they are beneficial.